Methodology to assess the vulnerability of hydrological systems to the potential effects of climate change - Orozco Medina, Ismael; Martínez Bárcenas, Adrián (Acta Universitaria, 2022)
There is uncertainty about the degree of vulnerability of a hydrological system to the effects of climate change, especially the possible alteration of the pluvial regime along with inefficient practices, overexploitation of aquifers, and inadequate water treatment. For this reason, this research focuses on determining current and future vulnerability of hydrological systems through a methodology that combines a distributed hydrological model, a general circulation model, a population growth model, artificial neural networks (ANN), and a series of indicators that describe the system comprehensively. This methodology has made it possible to project the system's vulnerability in the near future (the year 2035) for the RCP4.5, RCP6.0, and RCP8.5 scenarios. The results show that the system is already vulnerable and that the RCP4.5 scenario presents the highest vulnerabilities with high spatial and temporal variability.